Fundamentals of primary resection of acute colon cancer - Delgado, Bolívar (Cirugía del Uruguay, 2021)
In colonic cancer with acute ,complications, the conservative treatment consisting of staged operations, has shown very poor results. Such cases, according to the experience of different authors, as well as my own, during the last few years, have improved with primary resection. This technique has a higher resectability rate and a lower rate of morbimortality. Arguments for and against this procedure are discussed. In cancers of the left side, transit restoration is performed in the same procedure as primary resection, in selective cases. In the rigt slide cancer it is an almost compulsory procedure. There are cases wherein urgent primary resection becomes necessary and it is less controvertible. This resection is also the best paliative operation in cases of cancers with complications which also present liver metastasis.